Lasalocid or Rumensin to prevent lactic acidosis in cattle - Dennis, S.M.; Avery, T.B.; Bartley, E.E.; Galitzer, S.J.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station, 2011)
Lasalocid or Rumensin (monensin) protected cattle gorged with grain from lactic acidosis. Both lasalocid and monensin prevented the decrease in rumen and blood pH and increase in rumen and blood lactic acid (0(-) isomer) usually associated with lactic acidosis. Lasalocid appears more effective in preventing acidosis than monensin.
Keywords: Beef; Lactic acid; Lasalocid; Rumensin